2023
DOI: 10.1001/jamaoto.2022.3700
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Brief Tele–Cognitive Behavioral Treatment vs Attention Control for Head and Neck Cancer Survivors With Body Image Distress

Abstract: ImportanceAlthough 1 in 4 head and neck cancer (HNC) survivors experience clinically significant body image distress (BID), a psychosocial morbidity that adversely affects quality of life, effective interventions for these patients are lacking.ObjectiveTo evaluate the acceptability and preliminary efficacy of BRIGHT (Building a Renewed ImaGe after Head and neck cancer Treatment), a brief tele–cognitive behavioral therapy, at reducing BID among HNC survivors.Design, Setting, and ParticipantsThis parallel-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 47 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…The intervention consisted of five weekly CBT sessions with a psychologist via a telemedicine video platform (tele-CBT), workbook, and educational materials that included psychoeducation, self-monitoring, cognitive restructuring, coping strategies, and relapse prevention topics related to body image. 66 Compared with an attention control group, those participants in the tele-CBT group reported significantly less body image distress with a large effect size. 66 While these studies offer support for psychosexual counseling, none of the new psychosexual counseling studies reported adverse events.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The intervention consisted of five weekly CBT sessions with a psychologist via a telemedicine video platform (tele-CBT), workbook, and educational materials that included psychoeducation, self-monitoring, cognitive restructuring, coping strategies, and relapse prevention topics related to body image. 66 Compared with an attention control group, those participants in the tele-CBT group reported significantly less body image distress with a large effect size. 66 While these studies offer support for psychosexual counseling, none of the new psychosexual counseling studies reported adverse events.…”
Section: Resultsmentioning
confidence: 95%
“…66 Compared with an attention control group, those participants in the tele-CBT group reported significantly less body image distress with a large effect size. 66 While these studies offer support for psychosexual counseling, none of the new psychosexual counseling studies reported adverse events. Access because of a lack of insurance coverage or knowledgeable professionals continues to be a challenge for counseling-based interventions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The CONSORT diagram (eFigure 1 in Supplement 1), methods, and primary and secondary analyses for the RCT have been described in detail. 13,14 Results are reported according to the Consolidated Standards of Reporting Trials Extension (CONSORT Extension) reporting guidelines for randomized pilot and psychological intervention trials. 19,20…”
Section: Study Approvalsmentioning
confidence: 99%
“…[7][8][9] Cognitive behavioral therapy (CBT)-based approaches have emerged as potential treatment paradigms for HNC survivors with BID. 10,11 BRIGHT (Building a Renewed ImaGe after Head & neck cancer Treatment) is a brief tailored CBT that has demonstrated feasibility, acceptability, telehealth compatibility, and preliminary e cacy in both single-arm 12 and pilot randomized clinical trial (RCT) 13,14 settings. BRIGHT was developed to target maladaptive body image coping among HNC survivors.…”
Section: Introductionmentioning
confidence: 99%